PENGARUH PEMBERLAKUAN FREE TRADE ZONE TERHADAP PAJAK PERTAMBAHAN NILAI SERTA BEA IMPOR BARANG YANG MASUK KE AREA BATAM (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to examine the effect of the Free Trade Zone on Value Added Tax and Import Duty. The object of the this research is companies that have been registered with the Batam concession agency which are free from value added tax and import duty. The sample method is done by random sampling. The number of companies sampled in this study were 100 companies. The data used is secondary data in the form of data requested by intermediaries or third parties. The data analysis method used in this study is simple linier regression analysis. The results showed that the application of the Free Trade Zone had a significant effect on the exemption of value added tax and had a positive effect on the exemption of import duty. Keyword : Free Trade Zone, Exemption of Value Added Tax, Import Duty Exemption.